Pengaruh Efikasi Diri Dan Pengetahuan Kewirausahaan Terhadap Minat Berwirausaha Pada Siswa Kelas XI SMK Muhammadiyah Delanggu Tahun Ajaran 2015/2016 - Saputra, Rudi Wahyu, Drs. Nur Chusni, SE.,M.Ag (2016)
The purpose of this study was to determine: 1) The effect of self-efficacy toward entrepreneurship interest in class XI student of SMK Muhammadiyah Delanggu. 2) Effect of entrepreneurial knowledge of the interest in entrepreneurship in class XI student of SMK Muhammadiyah Delanggu. 3) Effect of entrepreneurial self-efficacy and knowledge of the interest in entrepreneurship in class XI student of SMK Muhammadiyah Delanggu. This research is descriptive research with quantitative data obtained derived from the image data sets. The population in this study were all class XI in SMK Muhammadiyah Delanggu academic year 2015. The sample was taken as 110 students with proportional random sampling. Necessary data obtained through questionnaires and documentation. The questionnaire previously tested and tested for validity and reliability were tested. Data analysis technique used is multiple linear regression analysis, t-test, F, and the relative contribution and effective. The results of the regression analysis obtained regression equation: Y = 4.117 + 0,313X1 + 0,581X2. The equation shows that the interest in entrepreneurship is influenced by the motivation to learn and learning environment. The conclusions drawn are: 1) Efficacy themselves against interest in entrepreneurship in class XI student of SMK Muhammadiyah Delanggu acceptable. This is based on multiple linear regression analysis (t test) note that tcount> ttable, 4.266> 1.980 and the significance value <0.05, namely 0.000 with the relative contribution of 30% and the effective contribution of 18.3%. 2) Knowledge of entrepreneurship against the interest in entrepreneurship in class XI student of SMK Muhammadiyah Delanggu acceptable. This is based on multiple linear regression analysis (t test) note that tcount> ttable, namely 8.107> 1.980 and the significance value <0.05, namely 0.000 with the relative contribution of 70% and the effective contribution of 42.6%. 3) Self efficacy and entrepreneurial knowledge to the interest in entrepreneurship in class XI student of SMK Muhammadiyah Delanggu acceptable. This is based on multiple linear regression analysis of variance (F test) is known that F count> F table, ie 83.290> 3.070 and the significance value <0.05, namely 0.000. 4) The coefficient of determination (R2) of 0.609 indicates that the influence of self-efficacy and knowledge of entrepreneurship to entrepreneurship interest in class XI student of SMK Muhammadiyah Delanggu amounted to 60.9%, while the rest influenced by other variables.